Framing realities : a critical analysis of perspectival distortion in the film Alice by Czech Surrealist Jan Švankmajer - Soutter, Simone (Rhodes University, Faculty of Humanities, Department of Fine Art)
My MFA exhibition Through the looking glass; altered states of perception, explores my experience of mental distress: Major Depressive Disorder (MDD), through the medium of painting and multimedia collage. Situated in the Main Fine Art building on Rhodes University campus, this practical submission takes the form of a collection of oil paintings accompanied by an immersive wall of collaged experimentations, depicting the perspectival shifts I have experienced in coping with mental distress. The paintings explore concepts of framing and perspective, both literally and metaphorically in unpacking how our perceptions are manipulated by the way in which situations and concepts are framed. I use strategies and techniques drawn from the Surrealist and Cubist movements in order to depict my distorted experience of time and space, but also to tap into my own unconscious. In this mini-thesis: Framing realities; A critical analysis of perspectival distortion in the film Alice by Czech Surrealist Jan Švankmajer, I explore the strategies and concepts developed during the Surrealist and Cubist movements in relation to strategies used by Švankmajer in his disturbing interpretation of Alice's Adventures into Wonderland. Here, he visually explores the psyche of an imaginative child. His unique interpretation is expressed through the combination of live-action film and stop-motion animation. I position my work in relation to themes proposed by Maurice Merleau-Ponty, Ernst Jentch, Sigmund Freud and Julia Kristeva. In the first Chapter: Framing and Perspectival shifts, I unpack framing and perspectival shifts exhibited in the Cubist (a physical shift), Dadaist (a social shift), and Surrealist (an unconscious shift) movements. In Chapter Two: A critical analysis of Alice by Jan Švankmajer, I engage in an analysis of themes (examined in the above art movements) relative to the film Alice. These are found objects and assemblages, ambiguity, distortion of scale, the Unconscious, the uncanny and multi-sensory modalities. Chapter Three: Through the Looking Glass; Altered states of perception, I discuss how the themes discussed in Chapter Two apply to my own body of work and how these themes are addressed with regards to my lived experience of mental disorder and distress.
Keywords: SÌŒvankmajer, Jan, 1934- -- Criticism and interpretation; Depression, Mental -- Exhibitions; Perception; Frames (Sociology); Surrealism -- Influence; Cubism -- Influence; Surrealism in motion pictures; Depression, Mental in art